Determination of Firm Value with Good Corporate Governance as Moderator - Arif Rahman; Darsono Darsono (Quantitative Economics and Management Studies, 2022)
Firm value can be determined by several indicators such as profitability ratios, capital structure, growth opportunity, company size and good corporate governance. It serves as a moderator of the company. This research is classified as quantitative descriptive statistical research and applies quantitative analysis research data applies pooling all manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2015-2019 as a population. So that the determination of the sample using purposive sampling technique. Data processing and hypothesis testing in this study apply multiple regression analysis through the help of SPSS (Statistical Product and Service Solution) software. The results obtained are the determination of firm value in terms of size, earnings management, and the company's capital structure